Identification and characterisation of a rare MTTP variant underlying hereditary non-alcoholic fatty liver disease - Jane I. Grove; Peggy C.K. Lo; Nick Shrine; Julian Barwell; Louise V. Wain; Martin D. Tobin; Andrew M. Salter; Aditi N. Borkar; Sara Cuevas-Ocaña; Neil Bennett; Catherine John; Ioanna Ntalla; et al. (JHEP Reports, 2023)
Background & Aims: Non-alcoholic fatty liver disease (NAFLD) is a complex trait with an estimated prevalence of 25% globally. We aimed to identify the genetic variant underlying a four-generation family with progressive NAFLD leading to cirrhosis, decompensation, and development of hepatocellular carcinoma in the absence of common risk factors such as obesity and type 2 diabetes. Methods: Exome sequencing and genome comparisons were used to identify the likely causal variant. We extensively characterised the clinical phenotype and post-prandial metabolic responses of family members with the identified novel variant in comparison with healthy non-carriers and wild-type patients with NAFLD. Variant-expressing hepatocyte-like cells (HLCs) were derived from human-induced pluripotent stem cells generated from homozygous donor skin fibroblasts and restored to wild-type using CRISPR-Cas9. The phenotype was assessed using imaging, targeted RNA analysis, and molecular expression arrays. Results: We identified a rare causal variant c.1691T>C p.I564T (rs745447480) in MTTP, encoding microsomal triglyceride transfer protein (MTP), associated with progressive NAFLD, unrelated to metabolic syndrome and without characteristic features of abetalipoproteinaemia. HLCs derived from a homozygote donor had significantly lower MTP activity and lower lipoprotein ApoB secretion than wild-type cells, while having similar levels of MTP mRNA and protein. Cytoplasmic triglyceride accumulation in HLCs triggered endoplasmic reticulum stress, secretion of pro-inflammatory mediators, and production of reactive oxygen species. Conclusions: We have identified and characterised a rare causal variant in MTTP, and homozygosity for MTTP p.I564T is associated with progressive NAFLD without any other manifestations of abetalipoproteinaemia. Our findings provide insights into mechanisms driving progressive NAFLD. Impact and Implications: A rare genetic variant in the gene MTTP has been identified as responsible for the development of severe non-alcoholic fatty liver disease in a four-generation family with no typical disease risk factors. A cell line culture created harbouring this variant gene was characterised to understand how this genetic variation leads to a defect in liver cells, which results in accumulation of fat and processes that promote disease. This is now a useful model for studying the disease pathways and to discover new ways to treat common types of fatty liver disease.